Effectiveness of Prophylactic Use of Hepatoprotectants for Tuberculosis Drug-Induced Liver Injury: A Population-Based Cohort Analysis Involving 6,743 Chinese Patients - Chen, Qin; Hu, Airong; Ma, Aixia; Jiang, Feng; Xiao, Yue; Chen, Yanfei; Huang, Ruijian; Yang, Tianchi; Zhou, Jifang (Frontiers in Pharmacology, 2022)
Abstract Background Tuberculosis drug-induced liver injury (TB-DILI) is a common and potentially severe adverse drug reaction leading to treatment interruption and treatment failure. The real-world preventive effectiveness of hepatoprotective agents for DILI is not well described. To evaluate the patterns of prophylactic therapies in real-world settings and risks of DILI among adult TB patients without known risk factors for DILI. Methods Population-based retrospective cohort study of patients receiving first-line anti-tuberculosis drugs in the Chinese Center for Disease Control and Prevention (CDC) TB registry linked to Ningbo Regional Health Care Database (NRHCD) between 2015 and 2020. The primary exposure was any use of chemopreventive agents including silymarin and/or glycyrrhetinic acid during 30-day period prior to TB diagnosis (index date). The main outcome measure was the occurrence of newly onset DILI following TB treatment. Eligible patients were followed until the earliest of any DILI, treatment discontinuation, death or end of study period (June 30, 2020). Marginal structural competing risk models and Cox models via inverse probability treatment weights using high dimensional propensity scores were used to estimate subdistribution hazard risks (SHR) and 95% confidence intervals (CI) for DILI risks, with adjustment for age, sex, TB-related characteristics and comorbidities. Results We identified a cohort of 6,743 adult patients with TB (mean age 47.1 [SD 18.7] years; 65.80% male), with 2,886 (42.8%) patients received hepatoprotective agents. A total of 895 DILI events and 111 all-cause death events without DILI were observed over a median follow-up of 367 days post-TB diagnosis. The incidence rates of composite outcome combining DILI and all-cause mortality were 248.9 and 222.3 per 1000 person-years in the hepatoprotective agent exposed and unexposed groups (Relative hazard ratio 1.35, 95% CI 1.11-1.64). The incidence rates of DILI were 223.7 and 196.1 per 1000 person-years in the hepatoprotective agent exposed and unexposed groups (Relative hazard ratio 1.38, 95% CI 1.12-1.71). Patients with any chemopreventive agents use had comparable liver function changes as evidenced by laboratory tests. Conclusions: A non-trivial number of adult patients received chemopreventive agents for TB-DILI. However, prophylactic utilization of hepatoprotective agents were not associated with reduction in TB-DILI risks.